Glass -polyalkenoate cement: An alternative material for kyphoplasty in osteoporotic vertebral compression fractures – An ex vivo study. (July 2018) - Leschinger, Tim; Engel, Karsten; Brüggemann, Gert Peter; Dederer, Viktoria; Neiss, Wolfram Friedrich; Scheyerer, Max Joseph; Müller, Lars Peter; Wegmann, Kilian
Abstract: Adjacent vertebral body fracture is described as a risk after vertebroplasty and kyphoplasty. It may be true that this phenomenon is caused precisely because of the frequently used polymethylmethacrylate cement (PMMA), which shows a higher level of stiffness than bone material and may ultimately lead to shifting stress levels within the entire spine. The goal of the present study was to evaluate and compare the pressure distribution in the endplate of human vertebrae after kyphoplasty with PMMA and aluminum-free glass-polyalkenoate cement (gpc). For the present study, 8 fresh frozen human cadaveric vertebral bodies from the thoracolumbar junction were used. All vertebrae were augmented transpedicularly on one side with gpc and on the other side with PMMA. A loading of 600 N, 800 N and 1000 N was applied. In the data processing an individual region of interest (roi) was generated for each vertebra. The following parameters were determined for each roi: maximum force [N], maximum pressure [kPa], mean pressure [kPa], roi area [cm 2 ]. We found significantly higher mean pressure values in the areas of the vertebrae augmented with PMMA, compared to the ones after augmentation with gpc (p = 0.012) when applying 1000 N. In the groups with lower forces there were no statistical relevant differences. The pressure distribution shows an advantage for gpc. A material, which does not create load concentration onto the cranial and caudal vertebral surface, could have major advantages concerning the risk of adjacent vertebral fractures. Thus the results of the 1000 N loading protocol suggest gpc being a possible alternative to ordinary PMMA cement, regarding its influence on stiffness in kyphoplasty. These and other general aspects like incorporation should be addressed and elaborated more detailed in further studies. Graphical abstract: 8 vertebral bodies were used in order to compare pressure distribution in the endplate of the human thoracolumar vertebrae after kyphoplasty with PMMA and glass-polyalkenoate-cement (gpc). The pressure distribution after application of physiological compression forces of 1000 N shows gpc as being superior to PMMA, suggesting it to be a promising material for the treatment of vertebral osteoporotic fractures by reducing the risk of adjacent vertebral fractures. fx1 Highlights: Pressure values in vertebral bodies augmented with PMMA and GPC were quantified. The pressure distribution after application of 1000 N shows clear advantage for GPC. GPC could be an alternative material for the augmentation in kyphoplasty. GPC could reduces the risk of adjacent vertebral fractures after kyphoplasty.